2021
DOI: 10.1093/jat/bkab067
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Gamma-Butyrolactone in JUUL Liquids

Abstract: Gamma-Butyrolactone (GBL), a commonly used industrial solvent, is used recreationally as a central nervous system (CNS) depressant and, therefore, a United States Drug Enforcement Agency (DEA) List 1 chemical of the Controlled Substances Act. GBL was identified presumptively in the liquid from JUUL Virginia Tobacco flavored pods during routine untargeted screening analysis of e-cigarette products by gas chromatography–mass spectrometry (GC–MS). Methods for the confirmation and quantitation of GBL were develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…While many known chemicals have been targeted for analysis, these methods may yet leave unsampled portions, leading to potential gaps in the understanding of ENDS aerosol composition. Apart from the work of a few research groups [35][36][37], little has been published on the NTA of nicotine-containing aerosol from combustible and heated tobacco products, and even less on ENDS aerosols [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…While many known chemicals have been targeted for analysis, these methods may yet leave unsampled portions, leading to potential gaps in the understanding of ENDS aerosol composition. Apart from the work of a few research groups [35][36][37], little has been published on the NTA of nicotine-containing aerosol from combustible and heated tobacco products, and even less on ENDS aerosols [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…125 Recently, GC-MS and LCMS-MS analysis of JUUL Liquids, the best-selling nicotine pods in the United States, detected low levels of GBL (0.37 mg/ml) in the Virginia Tobacco flavoured liquid when aerosolised. 129 This is likely a byproduct of the manufacturing process but illustrates again the insidious nature of the vape liquids, from reputable companies with quality controls in place.…”
Section: Gbl (Gamma-butyrolactone) and Ghb (Gamma Hydroxybutyric Acid)mentioning
confidence: 99%
“…In a recent toxicology study [22] into the metabolism of GHB in humans, doses between 33.1 and 60.1 mg/kg body weight were given in a series of 250 ml orange drinks, and levels as high as 80 mg/ ml GHB [23] have been reported in a near-fatal incident after the consumption of a so-called "health drink" in the UK. Recent studies of electronic cigarette vaping fluids showed some to have GBL levels as high as 0.37 mg/ml [24].…”
Section: Introductionmentioning
confidence: 99%